The J.H. Kwabena Nketia archive at the University of Ghana- Legon - Opoku-Boateng, J.; Cann, E.; Ntewusu, S.A.; Owusu, S. (History in Africa, 2020)
This report is on the J.H. Kwabena Nketia Archive at the University of Ghana, Legon, Accra. In the light of growing destruction of public archives in Ghana, mainly due to chieftaincy and land litigation but also because of the lack of a proper maintenance culture, this report will suggest that other, non-conventional archives, such as the J.H. Kwabena Nketia Archive should be explored by historians and researchers. This report highlights the contribution of J.H. Kwabena Nketia who sought to preserve information that is crucial at a time when the world seems to be abandoning most of the most important and significant aspects of Africa’s cultural and artistic history
Research Article
Keywords: audio-visual; Africa’s cultural and artistic history; chieftaincy; land litigation